The hard state, soft city of Singapore - Chung, Simone Shu-Yeng; Douglass, Mike (Asian cities (Amsterdam, Netherlands), 2020)
With Singapore serving as the subject of exploration, the volume explores the purview of imaginative representations of the city. Alongside the physical structures and associated practices that make up our lived environment, and the conceptualised space engineered into material form by bureaucrats, experts and commercial interests, a perceptual layer of space is conjured out of people's everyday life experiences. While such imaginative projections may not be as tangible as its functional designations, they are nonetheless equally vital and palpable. The richness of its inhabitants' memories, aspirations and meaningful interpretations challenges the reduction of Singapore as a Generic City. Taking the imaginative field as the point of departure, the forms and modes of intellectual and creative articulations of Singapore's urban condition probe the resilience of cities, and the people who reside in them, through the images they convey or evoke as a means for collective expressions of human agency in placemaking.